An autonomous vehicle sequencing problem at intersections: A genetic algorithm approach - Yan, Fei; Dridi, Mahjoub; El Moudni, Abdellah (Zielona Góra: Uniwersytet Zielonogórski)
This paper addresses a vehicle sequencing problem for adjacent intersections under the framework of Autonomous Intersection Management (AIM). In the context of AIM, autonomous vehicles are considered to be independent individuals and the traffic control aims at deciding on an efficient vehicle passing sequence. Since there are considerable vehicle passing combinations, how to find an efficient vehicle passing sequence in a short time becomes a big challenge, especially for more than one intersection.
Keywords: autonomous vehicles; autonomous intersection management; genetic algorithms; dynamic programming; heuristics